Microbial and chemical signatures of melting sea-ice: export of bacteria, microeukaryotes, and molecules - Magda G. Cardozo-Mino; Julian Merder; Thorsten Dittmar; Antje Boetius; Matthias Wietz (Deep Sea Research Part II: Topical Studies in Oceanography, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A decade of microbial community dynamics on sinking particles during high carbon export events in the eastern Fram Strait - Magda G. Cardozo-Mino; Ian Salter; Eva-Maria Nöthig; Katja Metfies; Simon Ramondenc; Claudia Wekerle; Thomas Krumpen; Antje Boetius; Christina Bienhold (Frontiers in Marine Science, 2023)
Marine sinking particles sequester atmospheric carbon dioxide to the deep ocean via the biological carbon pump. Understanding how environmental shifts drive changes in the microbial composition of particles, and how these affect the export of organic matter from the surface to the deep ocean, is critical, especially in the rapidly changing Arctic Ocean. Here, we applied next generation sequencing of the 18S and 16S rRNA genes to sediment trap samples from around 200 m water depth in the eastern Fram Strait, covering a time frame of more than one decade (2000-2012). The aim was to characterize their microbial composition during annual highest particulate organic carbon flux events. The bimodal annual spring and summer export fluxes were representative of the strong seasonality in the region. Furthermore, the study period was characterized by considerable interannual variation, marked especially by a warm water anomaly between 2005 and 2007. During this period changes in the hydrography and sea ice cover also led to measurable changes in the microbial composition of particles. The warm water period was marked by a decrease in diatoms affiliated with Chaetoceros , an increase of small phytoplankton and an increase in sequence abundance of the bacterial taxa Oceanospirillales , Alteromonadales and Rhodobacterales on the particles. The resulting changes in microbial composition and the associated microbial network structure suggest the emergence of a more developed retention system in the surface ocean. Our results provide the first long-term assessment of the microbial composition of sinking particles in the Arctic Ocean, and stress the importance of sea ice and hydrography for particle composition and subsequent flux of organic matter to deeper waters.

World Trade Center Site Exposure Duration Is Associated with Hippocampal and Cerebral White Matter Neuroinflammation - Chuan Huang; Minos Kritikos; Mario Serrano Sosa; Thomas Hagan; Alan Domkan; Jaymie Meliker; Alison C. Pellecchia; Stephanie Santiago-Michels; Melissa A. Carr; Roman Kotov; Megan Horton; Sam Gandy; et al. (Molecular Neurobiology, 2023)
Responders to the World Trade Center (WTC) attacks on 9/11/2001 inhaled toxic dust and experienced severe trauma for a prolonged period. Studies report that WTC site exposure duration is associated with peripheral inflammation and risk for developing early-onset dementia (EOD). Free Water Fraction (FWF) can serve as a biomarker for neuroinflammation by measuring in vivo movement of free water across neurons. The present case-controlled study aimed to examine associations between WTC site exposure duration as well as EOD status with increased hippocampal and cerebral neuroinflammation. Ninety-nine WTC responders (mean age of 56) were recruited between 2017 and 2019 ( N = 48 with EOD and 51 cognitively unimpaired). Participants were matched on age, sex, occupation, race, education, and post-traumatic stress disorder (PTSD) status. Participants underwent neuroimaging using diffusion tensor imaging protocols for FWF extraction. Region of interest (ROI) analysis and correlational tractography explored topographical distributions of FWF associations. Apolipoprotein-e4 allele ( APOE ε4) status was available for most responders ( N = 91). Hippocampal FWF was significantly associated with WTC site exposure duration ( r = 0.30, p = 0.003), as was cerebral white matter FWF ( r = 0.20, p = 0.044). ROI analysis and correlational tractography identified regions within the limbic, frontal, and temporal lobes. Hippocampal FWF and its association with WTC exposure duration were highest when the APOE ε4 allele was present ( r = 0.48, p = 0.039). Our findings demonstrate that prolonged WTC site exposure is associated with increased hippocampal and cerebral white matter neuroinflammation in WTC responders, possibly exacerbated by possession of the APOE ε4 allele.

New Fisheries-related data from the Mediterranean Sea (April 2015) - P.K. KARACHLE; A. BAŞUSTA; N. BAŞUSTA; D. BOSTANCI; K. BUZ; H. GIRGIN; I. CHATER; L. KOKOKIRIS; S. KONTAŞ; M.-H. KTARI; C.D. MARAVELIAS; G. MINOS; et al. (Mediterranean Marine Science, 2015)
In this second Collective Article with fisheries-related data from the Mediterranean Sea we present the evaluation of bony structures in aging of Barbus tauricus, otolith dimensions-body length relationships for two species (Trachinus draco and Synchiropus phaeton), information on the growth of juvenile Thunnus thynnus and of Ruvettus pretiosus, weight-length relationships for three species (Aulopus fiamentosus, Thunnus thynnus and Tylosurus acus imperialis) and data on feeding habits and reproduction of Aulopus fiamentosus.

New Mediterranean Biodiversity Records (April 2015) - Α. ΖΕΝΕΤΟΣ; E.H.KH. AKEL; C. APOSTOLIDIS; M. BILECENOGLU; G. BITAR; V. BUCHET; N. CHALARI; M. CORSINI-FOKA; F. CROCETTA; A. DOGRAMMATZI; M. DRAKULIĆ; G. FANELLI; et al. (Mediterranean Marine Science, 2015)
The Collective Article ‘New Mediterranean Biodiversity Records’ of the Mediterranean Marine Science journal offers the means to publish biodiversity records in the Mediterranean Sea. The current article is divided in two parts, for records of native and alien species respectively. The new records of native fish species include: the slender sunfish Ranzania laevis and the scalloped ribbonfish Zu cristatus in Calabria; the Azores rockling Gaidropsarus granti in Calabria and Sicily; the agujon needlefish Tylosurus acus imperialis in the Northern Aegean; and the amphibious behaviour of Gouania willdenowi in Southern Turkey. As regards molluscs, the interesting findings include Ischnochiton usticensis in Calabria and Thordisa filix in the bay of Piran (Slovenia). The stomatopod Parasquilla ferussaci was collected from Lesvos island (Greece); the isopod Anilocra frontalis was observed parasitizing the alien Pteragogus trispilus in the Rhodes area. The asteroid Tethyaster subinermis and the butterfly ray Gymnura altavela were reported from several localities in the Greek Ionian and Aegean Seas. The new records of alien species include: the antenna codlet Bregmaceros atlanticus in Saronikos Gulf; three new fish records and two decapods from Egypt; the establishment of the two spot cardinal fish Cheilodipterus novemstriatus and the first record of the Indo-Pacific marble shrimp Saron marmoratus in semi-dark caves along the Lebanese coastline; the finding of Lagocephalus sceleratus, Sargocentron rubrum, Fistularia commersonii and Stephanolepis diaspros around Lipsi island (Aegean Sea, Greece); the decapod Penaeus hathor in Aegean waters; the decapod Penaeus aztecus and the nudibranch Melibe viridis in the Dodecanese islands; the finding of Pinctada imbricata radiata in the Mar Grande of Taranto (Ionian Sea, Italy) and the Maliakos Gulf (Greece).

New Fisheries-related data from the Mediterranean Sea (April 2014) - K. STERGIOU; D.C. BOBORI; F.G. EKMEKÇİ; M. GÖKOĞLU; P.K. KARACHLE; G. MINOS; Y. ÖZVAROL; I. SALVARINA; A.S. TARKAN; L. VILIZZI (Mediterranean Marine Science, 2014)
As part of its policy, Mediterranean Marine Science started from 2014 to publish a new series of collective article with fisheries-related data from the Mediterranean Sea. In this first collective article we present length frequencies and weight-length relationships for the northern brown shrimp Farfantepenaeus aztecus in the eastern Mediterranean, length-weight relationships for 10 fish species in the North Aegean Sea, the feeding habits for 11 sparid fishes in the North Aegean Sea, a review of the existing literature on the feeding and reproduction of common carp Cyprinus carpio in Anatolia (Turkey) and mouth dimensions and the relationships between mouth area and length for seven freshwater fishes from Lake Volvi (Northern Greece).

Use of morphological differences for the identification of two picarel species Spicara flexuosa and Spicara maena (Pisces: Centracanthidae) - G. MINOS; A. IMSIRIDOU; G. KATSELIS (Mediterranean Marine Science, 2013)
The recognition and identification of the two species of Spicara genus (Spicara flexuosa, picarel and Spicara maena, blotched picarel) is difficult, due to a systematic confusion until now. In the present work a number of external morphometric features (ten body ratios) are evaluated for their diagnostic possibilities. According to Principal Component Analysis results, the body ratios head length to standard length, head height to head length and the ratios of two body heights, indicated that these characters were not related to the maturity stage of the species. The discriminant analysis based on the above body ratios, indicated rather high level of discrimination (83.2%) of the examined samples in two species. The results are discussed, and possibilities of improvement in the identification methodology for the two species are proposed.